School youth participation: ESEC as a model for the development of good socioeducational practices - Pérez de Guzman Puya, María Victoria; Trujillo-Herrera, Juan Francisco; Negrin-Power, Jauci; Dios-Rodríguez, Mónica (Comparative Cultural Studies: European and Latin American Perspectives, 2025)
The school is currently taking on a new social role as it faces increasingly complex demands that go beyond academic instruction, requiring comprehensive responses grounded in inclusive, democratic, and participatory approaches. This text explores how the educational system stands at a crossroads between its traditional instructional function and its broader social responsibility, particularly in vulnerable contexts. In this scenario, youth participation is presented as a central pillar of educational culture, essential for building fairer, more equitable, and community-connected school environments. This participation must be structural, sustained, and impactful—far from merely symbolic. From this perspective, the pilot experience of School and Community Social Education (ESEC) is highlighted as a reference model that promotes innovative and transformative socio-educational practices. ESEC fosters a culture of shared responsibility and youth leadership, while strengthening ties between schools, families, and communities. It also emphasizes the need for flexible structures and specialized professional profiles to effectively manage participation. Overall, this proposal seeks to redefine the school’s role as an agent of social change, capable of generating genuine and sustainable participatory processes that support democratic coexistence and collective well-being from an ethical and transformative perspective.